Comparative ontogenetic shape changes in the skull of Caiman species (Crocodylia, Alligatoridae) - Monteiro, L. R. [UNESP] (1997)
Ontogenetic shape changes in the skull of three species of the genus Caiman (C. latirostris, C. sclerops, and C. yacare) are compared by geometric morphometries for three-dimensional configurations (the least-squares analysis). The technique for obtaining the landmark coordinates is a simplification of the algorithm for multidimensional scaling. The ontogenetic nonlinear shape changes are similar in the three species but occur in a lesser extent in C. latirostris. These seem to be correlated with functional changes in the skull. The uniform shape change corresponds to an elongation of the skull, dorsoventral flattening, and lateral compression in C. sclerops and C. yacare. There is some lateral broadening in C. latirostris. Differences in the ontogenetic processes probably cause the differences in diet observed between C. latirostris and the other two species. Neotenic evolution seems to have acted in the skull of C. latirostris, and a posterior amplification of the early divergence led to a repatterning of the shape ontogenetic trajectory in this species.